Identifikasi Kekuatan Butt Joint dan Lap Joint pada Pengelasan Konstruksi Kapal - Bagiyo Suwasono; Muhammad Farizal; Nur Yanu Nugroho; Didik Hardianto (Universitas Trunojoyo Madura, 2023)
The joining of steel in ship construction was carried out through welding technology. One of the joining processes used two types of welded joints, namely butt and lap joints. This study identified the strength of the test material from ASTM A36 steel plates at welded joints by standardizing the tensile test. Experimental activities using a tensile testing machine and simulation activities using SolidWorks. The average tensile test values for butt and lap joints show yield strengths of 288.89 and 200 N/mm2, final strengths of 419.11 and 280 N/mm2, reduction of cross-sectional areas of 49.33 and 43.33%, strain 7% and 18.67%, modulus of elasticity 60.81 and 15 N/mm2. Tensile test simulations for butt and lap joints showed plastic deformation in the weld face, root, toe, and HAZ area. Experimental and simulated difference values for butt joints range from 941.67 to 1,519.67 N/m2, and lap joints range from 1,030 to 4,694 N/m2. The final results show that SMAW welding with the butt joint type has a higher strength value than the lap joint.